Edukasi Keamanan Digital dalam Penggunaan Dompet Digital di Kalangan Mahasiswa: Upaya Meningkatkan Kesadaran dan Keamanan Transaksi - Astri Rumondang Banjarnahor (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2025)
This study aims to enhance digital security literacy among Dompet Digital users. With the growing adoption of Dompet Digitals offering transactional convenience, digital security risks have also risen, especially among users with limited data protection awareness. The educational program focuses on introducing digital security risks, such as phishing, malware, and social engineering, along with providing protective strategies like two-factor authentication (2FA) and avoiding unsecured public Wi-Fi networks. The methods employed include socialization sessions, seminars, and workshops designed to build Dompet Digital users’ awareness in safeguarding their accounts. The program results indicate a significant increase in users' awareness and practical skills in identifying risks and implementing security measures. Additionally, users are expected to act as change agents, spreading this knowledge within their communities. Regular educational initiatives and collaboration with Dompet Digital providers are also recommended as ongoing steps to maintain digital security.